Comparative evaluation of the clinical and radiographic success of regenerative endodontic procedures in immature versus mature permanent incisors with apical periodontitis: A prospective observational study - Taruna Yadav; Shalini Garg; Anil Gupta; Sakshi Joshi; Shourya Tandon; Nishima Nishima (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of the study was to know the clinical and radiographic outcomes of regenerative endodontic procedures of immature versus mature in young permanent incisors with apical periodontitis. Methods: Twenty non-vital, young permanent incisors with traumatic exposure between the age of 7 and 13 years were taken. Patients were divided into two groups: Group I - immature (number of teeth included = 10) and Group II - mature (number of teeth included = 10). The procedure was performed by the blood clot method as a scaffold. Biodentine (about 2-3 mm) was placed as a capping material at the cementoenamel junction. Evaluation was based on the clinical (pain, sinus, tender on percussion, swelling, mobility, intact restoration) and radiographical (Nolla stage, thickening of walls, lamina dura continuity, calcification of pulp chamber and canal, periapical healing, PAI score) parameters. Results: All 19 teeth were clinically asymptomatic after the 12-month follow-up. Radiographically, the percentage of continuous root development (in the immature group) was 100% at 12 months (P = 0.000**). Radiography revealed a reduction in the PAI scores at 12 months in the immature and mature groups. None of the treated teeth responded to the cold test after a 12-month follow-up. One patient did not come for intervention in the mature group. All the statistical tests (Chi-square, Mann-Whitney U-test, and Fisher's exact test) were performed at a 5% significance level. Conclusion: Outcomes did not differ significantly between immature and mature groups.